Dinamização econômica e socioambiental na agricultura familiar: um estudo da cadeia produtiva da cajucultura no território Açu-Mossoró (RN) - França, Andreya Raquel Medeiros de (Universidade Federal Rural do Semi-Árido, 2016)
Family farming has gained more space in the Brazilian rural context. Investments through Public Policy have become the most valuable activity than in past times, along with the opening of institutional markets that favor the trade of its products, which has been increasingly diverse. In this perspective this study aims to analyze the dynamics of the internal structure of the production chain of cashew cultivation. The central question of this work is to understand how is the operation and viability of the production chain of cashew cultivation in family farming, considering its organizational, technological and environmental dynamism in the economic process of the Açu-Mossoró Territory (RN). The method used in this research was the study of the case in which the objective was to reach all households beneficiation who developed chestnut cutting activity in 2011, in the Açu-Mossoró Territory. The research universe consisted of census applied to 230 producers, totaling 27 rural communities in 04 municipalities of the territory: Assu, Serra do Mel, Mossoro and Porto do Mangue. To achieve results were applied forms the processing units and has been one georeferencing of these units. The purpose was to verify the social, economic and environmental relations. As a result it was possible to verify the fragile existing organizational structure in all municipalities that developed the activity in the territory. The activity was presented as economically viable, as the group studied was possible to calculate revenue of approximately R $ 20 million. The reality of the productive chain of cashew cultivation in the territory is unique, it is possible to identify two specific types of activities, where one side are the producers of cashew and those who only buy and cut your own brown, these achieve a high value addition to final product, managing to sell a kilogram at an average price R $ 22.50. And on the other hand, we have the weakest link, those who receive the raw cashew nuts from a middleman and outsource cutting without the aggregation of final value to the product, and in this case only receives the amount paid for each kilo of almonds, arriving to be registered R $ 0.80 paid per kilo of almonds. Finally, as a general analysis were obtained as satisfactory outcome the results, where it was possible to structure a picture of the current situation of the production chain of cashew cultivation in Açu-Mossoró territory, despite their impoverishment bottlenecks of labor relations, influence negative middleman in market access, lack technical assistance and access to public policies, organizational weakness caused mainly by the decline of collective organization models in recent years, in addition to loss-making relationships with environmental issues, demostrada from the disposal of solid waste more present in the activity that is the shell of the cashew nut. Thus, the productive chain of cashew cultivation in Açu-Mossoró Territory has proved to be a consolidated representation and economic activity for the
Revitalising economic and environmental in family farming : a chain of productive study of the territory cashew cultivation Açu - Mossoró (RN)
Keywords: Agroindústria; Sustentabilidade; Desenvolvimento territorial; Inovação; Agribusiness; Sustainability; Territorial development; Innovation; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE